2020
DOI: 10.1080/15384101.2020.1796036
|View full text |Cite
|
Sign up to set email alerts
|

Low glucose enhanced metformin’s inhibitory effect on pancreatic cancer cells by suppressing glycolysis and inducing energy stress via up-regulation of miR-210-5p

Abstract: (2020) Low glucose enhanced metformin's inhibitory effect on pancreatic cancer cells by suppressing glycolysis and inducing energy stress via up-regulation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 50 publications
3
19
0
Order By: Relevance
“…MiR-210 is a response binding element of HIF-1α. It has been reported that unstable blood glucose induced energy stress via up-regulating miR-210 in pancreatic cancer cells (35). Our finding provided the evidence that swing of glucose also induced abnormal expression of miR-210 in a mouse glomerular MCs cell line.…”
Section: Discussionsupporting
confidence: 74%
“…MiR-210 is a response binding element of HIF-1α. It has been reported that unstable blood glucose induced energy stress via up-regulating miR-210 in pancreatic cancer cells (35). Our finding provided the evidence that swing of glucose also induced abnormal expression of miR-210 in a mouse glomerular MCs cell line.…”
Section: Discussionsupporting
confidence: 74%
“…On the other hand, the potential beneficial effects of lownormal glucose levels has been far less investigated although there is preliminary in-vitro evidence (44,45). Whether efforts aimed at preventing hyperglycemia, either through dietary changes, such as the ketogenic diet (46) or medications, such as metformin, would favorably impact PDAC outcomes remains unclear; one study of metformin plus chemotherapy did not find a benefit (47).…”
Section: Discussionmentioning
confidence: 99%
“…Due to severe reduction of adenosine triphosphate (ATP) production, cancer cells become more susceptive to metformin-induced stress. Consequently, metformin may be more helpful in non-diabetic patients with pancreatic cancer [ 136 ].…”
Section: Pancreatic Cancermentioning
confidence: 99%